OXIDATION OF DISPERSE CARBON MATERIALS - V. H. Nguyen; A. S. Filimono; B. V. Peshnev; A. I. Nikolaev (Тонкие химические технологии, 2018)
It is proposed to consider the process of carbon materials oxidative activation from the positions of topochemical reactions involving chemisorption of the activating agent (oxidizer) on the material surface active centers followed by chemical interaction. Such an approach makes it possible to control the process of creating a carbon material with the desired characteristics of the porous space. It is assumed that the oxidizer chemisorption active centers are amorphous carbon, which is localized on the material crystallites boundaries. The change in the length of these boundaries will lead to a change in the process rate. It is shown that the number of such active centers on the carbon material surface depends on the size of the crystallites. It will have a significant impact not only on the rate of activation, but also on the possibility of the process flow on the surface or with porosity formation. Mathematical models describing the carbon sample specific surface changing in the oxidation process are proposed. They allow quantifying the proportion of carbon that is oxidized on the sample surface or with pores formation, as well as quantifying the number of pores. It is shown that the ratio of pore formation and surface oxidation processes depends on the oxidation temperature, the oxidizer nature and its flow rate. The proportion of porosity formation decreases with the increase in the oxidant flow rate and the increase in temperature. It was experimentally shown that in order to obtain a material with a more developed porous space and a high specific surface it is preferable to use carbon dioxide as an oxidizing agent.